A standard computable general equilibrium model for South Africa - Thurlow, James; van Seventer, Dirk (International Food Policy Research Institute, 2002)
The paper reports on the construction and testing of a Standard International Food Policy Research Institute (IFPRI) computable general equilibrium model for South Africa. A 1998 social accounting matrix (SAM) for South Africa is compiled using national accounts information and recently released supply-use tables. By updating to a recent year, and by distinguishing between producers and commodities, this SAM is an improvement on the existing SAM databases for South Africa. Furthermore, this SAM is made consistent with the requirements of IFPRI's standard comparative static computable general equilibrium (CGE) model. This model is then used to simulate the economy-wide impact of a range of hypothetical policy levers, including: increased government spending; the elimination of tariff barriers; and an improvement in total factor productivity. Results indicate that assumptions made regarding the mechanisms of macroeconomic adjustment are important in determining the expected impacts of these policies. Firstly, despite mixed results concerning changes in household income distribution, the impact of expansionary fiscal policy appears to be growth enhancing, with the Keynesian style adjustment mechanism producing the most positive results. Secondly, a complete abolition of import tariffs also appears to generate increases in gross domestic product, with negative and positive consequences for aggregate manufacturing and services respectively. Finally, an increase in total factor productivity is growth enhancing, with the most positive results derived under neoclassical assumptions of the macroeconomic adjustment mechanisms. These simulations are meant to demonstrate the usefulness for economy-wide policy modelling and the paper concludes by highlighting areas of policy analysis that might benefit from more detailed applications with this framework." -- Author's Abstract.